Analysis of the Publications of the Gandhigram Rural Institute: A Bibliometric Study - Tamizhchelvan, M.; Dhanavandan, S. (Journal of Information and Knowledge, 2015)
This paper aims to bring out the publications by the Gandhigram Rural Institute through Scopus database. It is found 1328 publications are published from 1968-2015 and analysed them. Various tools for bibliometric study are used for frequency, citation analysis, authorship pattern. It is found that the Collaborative Index is very high with 3.60 and 3.08, 3.00 in the years 1998, 1997 and 1990 respectively. It is observed from the table that CC and MCC is showing growing trends after 1990.